(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2018)
This paper discusses Anglicism issues in Malay translations of printed catalogues in English. The research data is made up of 2,064 headlines collected manually from Cosway and Avon printed catalogues. This study uses an eclectic approach to analyse the research data collected. Therefore, for the purpose of data collection and analysis, this study utilises and modifies the loanword category in the Malay language proposed by Heah (1989) and Puteri Roslina (2012), and adopts Haugen’s (1972) definition of loanwords, to classify Anglicism that exist in the translation version of advertising headlines. The findings show that translation, especially through the transference procedure, contributes to Anglicism in the said headlines. Loanwords can be classified into six types, namely unassimilated loanword, partially assimilated loanword, wholly assimilated loanword, orthographically assimilated loanword, assimilated compound loanword and truncated loanword. Based on the study conducted, the implication is translation contributes towards the existence of Anglicism in the translated version of Malay printed catalogues, which can be explained from positive and negative impacts. Makalah ini membincangkan isu keinggerisan yang wujud dalam katalog bercetak berbahasa Melayu versi terjemahan. Data kajian terdiri daripada 2,064 tajuk utama yang dikutip secara manual daripada katalog bercetak Cosway dan Avon. Kajian ini menerapkan pendekatan eklektik untuk menganalisis data kajian yang dikumpulkan. Bagi tujuan menganalisis data, kajian ini mengaplikasikan kategori kata pinjaman Heah (1989) dan Puteri Roslina (2012) yang diubah suai, serta definisi kata pinjaman oleh Haugen (1972) untuk mengelaskan unsur keinggerisan yang wujud dalam tajuk utama. Dapatan kajian menunjukkan bahawa langkah penterjemahan, khususnya melalui penggunaan prosedur peminjaman telah mewujudkan unsur keinggerisan dalam tajuk utama versi terjemahan. Kategori kata pinjaman pula boleh dikategorikan kepada enam kategori, iaitu kata pinjaman tidak asimilasi, kata pinjaman separa asimilasi, kata pinjaman asimilasi lengkap, kata pinjaman asimilasi ortografi, kata pinjaman majmuk asimilasi dan kata pinjaman asing yang dipendekkan. Berdasarkan kajian yang telah dilakukan, implikasi kajian ini memperlihatkan penterjemahan menyumbang ke arah kesan keinggerisan dalam katalog bercetak versi terjemahan berbahasa Melayu, yang boleh dihuraikan daripada segi kesan positif dan negatif.